Instagram Marketing for Business Promotion by SMEs : Evidence from the Republic of Karelia - Pavlova, Anna (Jyväskylän ammattikorkeakoulu, 2018)
The key topic of the present paper was Instagram marketing for business promotion. Nowadays, Instagram sets new trends in the world of marketing and proclaims new values. The platform has become not only a popular social network, but also a power-ful tool for business promotion. It provides great opportunities for brands to market their products and services, grow communities and build relationships with customers. Therefore, it piqued the author’s interest to examine how Instagram was viewed by micro, small and medium-sized enterprises based in the Republic of Karelia. The major objective was to explore the way Instagram marketing was implemented by SMEs in Karelia. The author’s intention was to determine for which business purposes they utilized Instagram and what approach to and attitude towards Instagram market-ing they had. The research was both descriptive and exploratory in nature and required qualitative data to address the research questions. Academic literature, articles and online publica-tions were used as a source of secondary data. Semi-structured interviews were chosen as the method to collect the primary data. The author conducted ten interviews with the representatives of SMEs based in Karelia that used Instagram for business promo-tion. The study revealed fundamental differences in approaches to and attitude towards Instagram marketing based on the organizations’ size. Small and medium-sized firms managed their Instagram accounts strategically and professionally and, as a result, achieved higher results. In conclusion, the author offered recommendations to the managers and owners of micro enterprises.